2022
DOI: 10.1590/fst.15221
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin treatment in the postharvest storage of pitaya fruits delays senescence and regulates reactive oxygen species metabolism

Abstract: Pitaya fruits have high senescence rates throughout their postharvest storage period. Additionally, studies have confirmed that melatonin plays a regulatory role in plant senescence. However, the involvement of melatonin in the postharvest senescence of fruits remains unclear. In this study, two cultivars of pitaya fruit, 'Zihonglong' and 'Jinghonglong' , were treated with melatonin and then evaluated for characteristics of senescence while in storage for 10 days. The results showed that melatonin treatment de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Pitaya fruit is highly perishable throughout postharvest storage due to the high moisture content present in the pulp. A study indicated that melatonin treatment effectively delayed fruit deterioration by reducing respiration intensity and oxygen radical production [14]. However, little information is known regarding the physicochemical changes that occur during fruit growth and maturation Foods 2021, 10, x FOR PEER REVIEW 2 of 22 linoleic acid, extracted from pitaya seeds have been reported to have laxative activity on gastroenteritis [11].…”
Section: Pitaya Species and Maturationmentioning
confidence: 99%
“…Pitaya fruit is highly perishable throughout postharvest storage due to the high moisture content present in the pulp. A study indicated that melatonin treatment effectively delayed fruit deterioration by reducing respiration intensity and oxygen radical production [14]. However, little information is known regarding the physicochemical changes that occur during fruit growth and maturation Foods 2021, 10, x FOR PEER REVIEW 2 of 22 linoleic acid, extracted from pitaya seeds have been reported to have laxative activity on gastroenteritis [11].…”
Section: Pitaya Species and Maturationmentioning
confidence: 99%
“…Postharvest decay is the main limiting factor for commercial value and shelf life of pitaya fruit ( Xu et al, 2021 ), which causes 40–50 % loss of postharvest fruit due to pathogen contamination and improper postharvest handling ( Bordoh, Ali, Dickinson, Siddiqui, & Romanazzi, 2019 ). Several approaches, such as cold storage, edible-coating, X-ray, plant hormones, antioxidation additives and antimicrobial agents, have been reported to resist postharvest diseases and hold fruit quality ( Ba et al, 2022 , Xu et al, 2021 ). However, these treatments are basic means of delaying fruit senescence and retaining flavor characteristics to various degrees after pathogenic invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Some metabolic activities, such as transpiration and respiration, the main factors influencing the increase of weight loss and decrease of firmness with the extension of storage time, occurred in postharvest jujube fruits ( Lufu, Ambaw & Opara, 2020 ; Park et al, 2015 ; Yang et al, 2021 ). Recently, studies on strawberry ( Liu et al, 2018 ), pitaya ( Ba et al, 2021 ), peach ( Gao et al, 2016 ) and plum ( Yan et al, 2022 ) showed that exogenous melatonin significantly inhibited the increases in decay and water loss, and the decline in firmness. In the present study, firmness had the strongest positive correlation with crisp fine fruits and negative correlation with crisp rotten, soft and rotten fruits, while weight loss was just the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, exogenous melatonin of 50, 200 and 400 µM delayed the decline of AsA content in postharvest fruits at 15 d. As seen by correlation analysis, high level of AsA content was correlated with decline in weight loss and increase in firmness of jujube fruits treated with melatonin, thereby indirectly affect visual appearance. Similarly, application of exogenous melatonin resulted in higher AsA contents in plum ( Bal, 2019 ), peach ( Gao et al, 2016 ), pitaya ( Ba et al, 2021 ) and tomato ( Liu et al, 2016 ). It was speculated that the decrease in the AsA content may be related to triggering of ASA-GSH cycle to enhance the cold tolerance of jujube fruit ( Miranda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%